2020
DOI: 10.21613/gorm.2020.1023
|View full text |Cite
|
Sign up to set email alerts
|

The Post-Discharge Growth of Very Low Birth Weight Preterm Infants

Abstract: <p>OBJECTIVE: In the present study, we investigate the growth characteristics of very low birth weight premature infants of up to two years corrected age, considering the factors affecting growth and catch-up growth time.</p><p>STUDY DESIGN: The demographic data, clinical features, and comorbidities of 77 preterm infants with birth weights of less than or equal to 1.500 g were examined, the infants’ growth statuses in the 40th gestational week (gw) and at 6, 12, 18 and 24 months the corrected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The difference between the growth parameters at 2.5 month and at 3.5 months were statistically significant (p<0.01). Ozdemir et al [17] (2020) revealed the mean difference between birth weight at 2.5 months and weight at 3.5 months was 1.578 kg. The mean difference between length at 2.5 months and length at 3.5 months was 8.471 cm [17].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The difference between the growth parameters at 2.5 month and at 3.5 months were statistically significant (p<0.01). Ozdemir et al [17] (2020) revealed the mean difference between birth weight at 2.5 months and weight at 3.5 months was 1.578 kg. The mean difference between length at 2.5 months and length at 3.5 months was 8.471 cm [17].…”
Section: Discussionmentioning
confidence: 98%
“…Ozdemir et al [17] (2020) revealed the mean difference between birth weight at 2.5 months and weight at 3.5 months was 1.578 kg. The mean difference between length at 2.5 months and length at 3.5 months was 8.471 cm [17].…”
Section: Discussionmentioning
confidence: 98%